Liquid–Liquid Extraction of Indicator Dyes into Imidazolium based Ionic Liquids - Mahajan, Suchita (My University, 2015)
Dyed wastewater, generated by textile industries is one of the main current issues contributing to water pollution. This is due to the consumption of large amounts of dyes, textile auxiliaries and chemicals thereby discharging high volumes of polluted water containing trace metals such as Cr, As, Cu and Zn, which are capable of harming the human health and environment. The wastewaters originating from dyeing processes are generally characterized by the high content of color caused by the dyestuffs; salts; chemical oxygen demand (COD) deriving from additives such as acetic acid, detergents and complexing agents; suspended solids including fibers; high temperature and broadly fluctuating pH. Various researches have been carried out the treatment of these dyed effluents keeping in mind their harmful effects towards the environment and aquatic biota. Dye removal using Ionic Liquid (IL) is one such technique, which is still not employed on an industrial scale but has been found to be a capable dye extracting agent from textile wastewater. Since the potential of Ionic Liquid for this application is still at surface level, the major economic concerns such as process efficiency and improvement in the amount of dye removed with minimal usage of Ionic Liquid has also been kept in mind. In the present work, a novel process, Ionic Liquid–Based Dispersive Liquid–Liquid Extraction (IL–DLLE) has been adapted for the removal of anionic (Eriochrome black T & Methyl orange) and cationic (Crystal violet & Malachite green) indicator dyes namely from aqueous solution. Three Imidazolium based Ionic Liquids ([C6mim][PF6]), ([C6mim][BF4]) and ([C4mim][PF6]) have been used for this purpose. High extraction efficiencies were observed for anionic dyes using [C6mim][BF4] IL while [C4mim][PF6] IL showed best results for cationic dyes. Out of all the studied dyes, maximum and minimum extraction efficiencies were obtained for Eriochrome black T and Methyl orange respectively.To make the process economical, used IL was regenerated by Reverse Dispersive Liquid–Liquid Extraction process. Two acid stripping solutions were employed for this purpose. The IL was successfully regenerated from the IL+ dye mixture and re-used for the extraction of fresh dye solutions. The regenerated ILs also resulted in high extraction efficiencies for all the dyes studied. On the basis of these results, IL–DLLE was found to be an efficient, simple, economical and fast method for dye extraction.
MT, SEE
Keywords: liquid-liquid extraction; Ionic liquids; Imidazole; Indicator dyes; SEE